Avaliação da segurança contra incêndios de sistemas de compartimentação vertical em fachadas cortina - Pasqualotto, Fernando Luis (Universidade do Vale do Rio dos Sinos, 2020)
The wide application of glass facades in vertical buildings is a concern when it comes to fire safety. This system loses its integrity easily and facilitates the spread of fire between vertical compartments. In order to guarantee the vertical isolation of adjacent compartments in this type of building, Brazilian standards provides passive protection provisions, such as fireproof sealing, horizontal extensions of 0.90 m and vertical extensions of 1.20 m, using non-combustible elements. In several countries, it is well known that sealing fire between floors is an effective measure to prevent the internal vertical spread of fire which become a necessary passive protection measure in curtain walls. However, there has been limited consensus regarding the dimensions, position, and shape of these horizontal and vertical extensions. This study presents an assessment of the fire behavior of different vertical compartment models with curtain walls according to the ASTM E2307 (ASTM, 2020) test using Pyrosim / FDS® software. After model calibration, eight compartment models were simulated, four using vertical projection and four using horizontal extension. Results showed that compartments with horizontal extensions were more effective with smaller dimensions when compared to vertical projections. A horizontal extension of 0.90 m has the ability to isolate the spread of fire between two adjacent rooms. A horizontal extension of 0.60 m is more effective than a vertical projection of 1.20 m. A horizontal extension of 0.40 m has an efficiency close to a vertical projection of 1.20 m. Therefore, current requirements by Brazilian standards do not present the same effectiveness when compared to each other.
Keywords: Fachada de vidro; Propagação vertical; Simulação computacional; Glass façade; Vertical propagation; Computational simulation; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo